2021
DOI: 10.3390/e23070823
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Patients with Varying Degrees of Coronary Artery Stenosis by ECG and PCG Signals Based on Entropy

Abstract: Coronary heart disease (CHD) is the leading cause of cardiovascular death. This study aimed to propose an effective method for mining cardiac mechano-electric coupling information and to evaluate its ability to distinguish patients with varying degrees of coronary artery stenosis (VDCAS). Five minutes of electrocardiogram and phonocardiogram signals was collected synchronously from 191 VDCAS patients to construct heartbeat interval (RRI)–systolic time interval (STI), RRI–diastolic time interval (DTI), HR-corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…A limitation of this study is that only PCG will be used, without simultaneously recorded ECG. In many studies, ECG was used as reference for PCG cycle segmentation 38. However, in recent years, some studies have shown that segmentation may not be necessary when deep learning is used for cardiac sound classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of this study is that only PCG will be used, without simultaneously recorded ECG. In many studies, ECG was used as reference for PCG cycle segmentation 38. However, in recent years, some studies have shown that segmentation may not be necessary when deep learning is used for cardiac sound classification.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, ECG was used as reference for PCG cycle segmentation. 38 However, in recent years, some studies have shown that segmentation may not be necessary when deep learning is used for cardiac sound classification. By using Shapley values and occlusion maps, Dissanayake et al 17 showed that deep learning methods can automatically emphasise the components on PCG data that make significant contribution to the classification.…”
Section: Discussionmentioning
confidence: 99%
“…More recently (2021), Zhang et al [60] classified patients into varying degrees of diameter reduction by combining ECG and PCG signals and calculating a number of entropy measures which were combined in a support vector machine (SVM). Also in 2021, Khan et al [61] along with Iqtidar et al [62] classified patients into one of four categories: normal, single-, dual-, or triple-vessel disease, whereas Mushtaq et al [63] only classified into diseased groups.…”
Section: Classification Of Cad Severitymentioning
confidence: 99%